The relationship between HIV and fertility in the era of antiretroviral therapy in sub Saharan Africa – Evidence from 49 Demographic & Health Surveys - Marston,M; Zaba,B; Eaton,JW (Tropical Medicine and International Health, 2017)
ObjectivesTo describe regional differences in the relative fertility of HIV-positive vs. HIV-negative women and changes as antiretroviral treatment (ART) is scaled up, to improve estimates of predicted need for and coverage of prevention of mother-to-child transmission services at national and subnational levels.MethodsWe analysed 49 nationally representative household surveys in sub-Saharan Africa between 2003 and 2016 to estimate fertility rate ratios of HIV-positive and HIV-negative women by age using exponential regression and test for regional and urban/rural differences. We estimated the association between national ART coverage and the relationship between HIV and fertility.ResultsSignificant regional differences exist in HIV and fertility relationships, with less HIV-associated subfertility in Southern Africa. Age patterns of relative fertility are similar. HIV impact on fertility is weaker in urban than rural areas. For women below age 30, regional and urban/rural differences are largely explained by differences in age at sexual debut. Higher levels of national ART coverage were associated with slight attenuation of the relationship between HIV and fertility.ConclusionsRegional differences in HIV-associated subfertility and urban–rural differences in age patterns of relative fertility should be accounted for when predicting need for and coverage of PMTCT services at national and subnational level. Although HIV impacts on fertility are somewhat reduced at higher levels of national ART coverage, differences in fertility between HIV positive and negative remain, and fertility of women on ART should not be assumed to be the same as HIV-negative women. There were few data in recent years, when ART has reached high levels, and this relationship should continue to be assessed as further evidence becomes available.